2019
DOI: 10.1002/dc.24210
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers to diagnose metastatic breast carcinoma to the pancreas: A case report and update

Abstract: The patient is a 72‐year‐old female who presents with new onset jaundice. The patient has a past medical history significant for right‐sided estrogen receptor (ER)‐positive and left‐sided ER‐negative breast cancers in 2005 and 2009, respectively, and recent 1‐year history of ER‐positive right‐sided breast cancer with bone and brain metastases. CT scan and endoscopic ultrasound (EUS) revealed a new 2 cm mass in the head of the pancreas, leading to EUS‐guided fine‐needle aspiration of the lesion. Pathologic work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, it is not uncommon to see the conversion of hormone receptors from the primary sites (up to 36%) and the diagnosis cannot be ruled out by negative staining. 20 , 21 , 22 Based on our search of literature in PubMed 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 and the literature review performed by Apodaca‐RuedaI et al in 2019 11 on the topic of pancreatic metastases from breast cancer, there are total 51 reported cases including our four cases of metastatic breast carcinomas to the pancreas, with 22 lobular and 29 ductal carcinomas. Among these 51 cases, 30 cases including current 4 cases have reported biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not uncommon to see the conversion of hormone receptors from the primary sites (up to 36%) and the diagnosis cannot be ruled out by negative staining. 20 , 21 , 22 Based on our search of literature in PubMed 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 and the literature review performed by Apodaca‐RuedaI et al in 2019 11 on the topic of pancreatic metastases from breast cancer, there are total 51 reported cases including our four cases of metastatic breast carcinomas to the pancreas, with 22 lobular and 29 ductal carcinomas. Among these 51 cases, 30 cases including current 4 cases have reported biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…GATA3 expression and an ERBB2 mutation (I767M) originating from a breast tumour were detected using immunohistochemistry and molecular diagnostics. The functional significance of this gene mutation has not been determined [95].…”
Section: Metastases To the Pancreasmentioning
confidence: 99%
“…Comprising just 2-5% of pancreatic tumors overall, metastases to the pancreas is a rare event [122]. Of these, the breast is the source of only 3-5% of these metastases [123]. Owing to this, genetic analyses of BC metastases to the pancreas are limited.…”
Section: Pancreatic Metastasismentioning
confidence: 99%
“…Owing to this, genetic analyses of BC metastases to the pancreas are limited. One study [123] investigating biomarkers for BC to pancreas metastasis identified a ERBB2 I767M mutation within the pancreatic tumor consistent with BC origin. This gene mutation's functional significance is undetermined.…”
Section: Pancreatic Metastasismentioning
confidence: 99%